Quantifying the impact of food safety criteria included in the Canadian Food Inspection Agency risk assessment model for food establishments through Expert Elicitation. (October 2018) - Racicot, Manon; Zanabria, Romina; Leroux, Alexandre; Ng, Sunny; Cormier, Mathieu; Tiwari, Ashwani; Aklilu, Solomon; Currie, Ryan; Arsenault, Julie; Griffiths, Mansel; Holley, Rick; Gill, Tom; et al.
Abstract: The Canadian Food Inspection Agency (CFIA) is developing a risk assessment model aimed at quantifying the food safety risk associated with food establishments under its jurisdiction. To support the development of this model, the current study was undertaken to quantify the relative importance of selected criteria considered for inclusion in the model. This process also aimed at estimating the risk associated with specific clusters of criteria. Overall, 173 criteria were presented to experts during a two-round face-to-face expert elicitation to estimate their relative risk to human health. Twenty-nine Canadian experts participated in the expert elicitation including members from academia (31%), industry (31%), and government (38%). A good consensus on the relative risks given to most criteria and clusters of criteria was achieved, and experts assessed them as significantly affecting the risk related to a food establishment. None of the experts expressed opposition to the inclusion of any criterion or to the way they were clustered. Experts assigned a relative risk of ≤4, of 4–8, and of ≥8–67% (116), 29.5% (51), and 3.5% (6) of the 173 criteria identified, respectively. Those having the highest impact on establishment food safety risk were: historical food safety recalls and lack of compliance for the sanitation program, the control of critical control points, followed by the equipment maintenance and calibration program, and the general food hygiene program. Having a sampling plan with trend analysis and follow-up actions was considered as an important mitigation factor. As a result, the median values calculated for each criterion and cluster will be used in the new Canadian Food Inspection Agency Establishment-based risk assessment model to support the allocation of inspection resources based on risk. Highlights: This study quantifies criteria for a risk assessment model for food establishments. The intent is to assess the food safety risk of food establishments. Recalls and lack of compliance with Preventive Control Plan had the highest impact. Results will be used to support the allocation of inspection resources based on risk.